Monetary stimulus amid the infrastructure investment spree: Evidence from China's loan-level data - Kaiji Chen; Haoyu Gao; Patrick Higgins; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2020)
We study the impacts of the 2009 monetary stimulus and its interaction with infrastructure spending on credit allocation. We develop a two-stage estimation approach and apply it to China's loanlevel data that covers all sectors in the economy. We find that except for the manufacturing sector, monetary stimulus itself did not favor state-owned enterprises (SOEs) over non-SOEs in credit access. Infrastructure investment driven by nonmonetary factors, however, enhanced the monetary transmission to bank credit allocated to local government financing vehicles in infrastructure and at the same time weakened the impacts of monetary stimulus on bank credit to non-SOEs in sectors other than infrastructure.
Keywords: E5; E02; C3; C13; 330; infrastructure investment; monetary policy transmission; fiscal shocks; policy interaction; credit reallocation; LGFVs